A simulation model with verification and validation for time-phased education planning in Afghanistan. (July 2014) - Marlin, Benjamin; Sohn, Han-Suk
Decision-makers have rightly come to expect thorough, relevant analysis prior to allocating resources. The field of education planning is no different in its requirement for such analysis. In this research, we present a discrete event simulation model in which individual students and teachers flow through the Afghanistan education system across a variable time horizon. We explain the simulation and its premises through some verification and validation processes that allow the user to glean insight into the implications of security, policy, and infrastructure in this complex and capricious environment.